PERBANDINGAN SUMBER PENDANAAN ANTARA LEASING DAN HUTANG BANK TERHADAP KEUNTUNGAN PERUSAHAAN PT. ASIADRILL BARA UTAMA BALIKPAPAN - Dewi, Septira (EKONOMIA, 2013)
PT. Asiadrill Bara Utama is a company engaged in drilling operations in the mining and petroleum industry-. Machinery and vehicles needed funds in large numbers because of the existence of a project done in a variety of locations. To support the project activities in the Sanga-Sanga company will add cars to the type of Ford Ranger 4x4 Single cabin MT using 2.2-liter turbo diesel engine which is powerful.The problem in this paper is whether the ownership of the vehicle Ford Ranger PT. Asiadrill Bara Utama is leasing more profitable than bank debt with car ownership hypothesis Ford Ranger 4x4 Single cabin using lease financing will be favorable when compared with the use of debt financing Bank.Analysis tool used is the use of leasing and NPV NPV using bank debt. The results: Berdasarkah IRR calculation results with Disconto estimates by 5% and 10% obtained NPV1 of Rp. And NPV2 Rp 11,069,199.00 - 21,529,458.00, the obtained value of IRR is 19.48%Hypothesis is accepted because the NPV using the leasing of Rp. 148,536,273.60 less than the NPV using a bank loan of Rp. 245.251.811.69.Thus, the company may choose to use the services of the project Leasing company.